Intermittent reproduction, mortality patterns and lifetime breeding frequency of females in a population of the adder (Vipera berus) - Dirk Bauwens; Katja Claus (PeerJ, 2019)
Female adders (Vipera berus) are “capital breeders” that exhibit delayed maturity and intermittent reproductive frequency. We studied the attainment of sexual maturity, the initiation of annual breeding in mature females, the energy and mortality costs associated with breeding, the length of the reproductive cycle and female lifetime reproductive frequency. We use longitudinal data obtained during an 18-year (2000–2017) mark–recapture study in a large population of adders in northern Belgium. A minority (15%) of the females gave birth to their first litter when they attained the actual age of 3 years, upon surpassing a minimum snout-vent-length of 38 cm. However, most females reproduced for the first time when they were 4 years or older. In mature females, breeding in a given year depends to a large extent on their body condition at the onset of the active season, indicating that a threshold level of energy reserves is necessary to start a reproductive cycle. During breeding years females stop growing, lose about one-third of their initial body mass and are very emaciated after parturition. The decrease in relative body mass was most notable initially in the largest and fattiest females. During the non-breeding years, females forage intensely to rebuild their fat reserves; their abilities to do so will strongly affect whether and when they engage in subsequent reproductive bouts. We used a multistate mark–recapture analytical method to simultaneously estimate the capture and survival rates of breeding and non-breeding females, a necessary procedure to obtain accurate estimates of survival probabilities. The analysis indicated much higher capture rates during the breeding years, but did not reveal a substantial effect of reproductive state on annual survival rates. Although some females were observed to breed in successive years, the reproductive cycle was most often biennial or triennial. However, most females (ca. 70%) that attained sexual maturity reproduced only once during their lifetime, while a minority of the females (ca. 5%) were observed to breed on 3–5 annual occasions. On average, females produced only ca. 1.3 litters during their reproductive lifetime. The short reproductive lifetime is a consequence not only of mortality directly related to the reproductive activities, but also of mortality associated with recovering from the weakened post-parturient body condition during the long intervals (1–2 years) between reproductive bouts.